Perilaku Keuangan Mahasiswa: Financial Technology, Literasi Keuangan, dan Gaya Hidup - Usmiatul Azizah; Lilik Sri Hariani; Walipah Walipah; Sulistyo Sulistyo (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2026)
The development of digital technology and student lifestyle trends are changing the mindset and methods of the younger generation in managing their finances. However, this change needs to be balanced with increased financial literacy, which plays a crucial role in shaping more rational and planned financial behavior. The research focuses on analyzing the influence of financial technology, financial literacy, and lifestyle on the financial behavior of students at the Faculty of Economics and Business, Universitas PGRI Kanjuruhan Malang. The ongoing research applies a quantitative descriptive approach involving 85 students from the Economics, Management, and Accounting Education study programs as the research sample. Simple random sampling was chosen as the sampling method in this study, while the data collection stage was carried out through the distribution of closed questionnaires. Data analysis was carried out through multiple linear regression that has passed the classical assumption test. Referring to the analysis findings, it was found that financial technology, financial literacy, and lifestyle simultaneously significantly influence students' financial behavior. However, individually, only financial literacy has a significant effect.